THE INFLUENCE OF TAM FACTORS ON THE INTEREST OF PAY LATER USERS - Thomas Stefanus Kaihatu (FEB Universitas Sam Ratulangi Manado, 2023)
As technology develops, people can do it digitally or online, namely Internet Banking, mobile banking, or call centers operated directly by artificial intelligence, one of which is Pay later. The public quickly recognizes Pay later due to technological advances in payment systems in e-commerce. This study aims to determine the effect of perceived ease of use, perceived usefulness, perceived risk, security, and trust on the interest of Pay later users. The study was conducted on 260 active pay later users aged 25-40 years, 158 female respondents, and 102 male respondents domiciled in DI Yogyakarta, DKI Jakarta, West Java, Central Java, and East Java. With probability sampling technique was applied to determine the number of samples. The results are based on the multiple linear regression method, which shows that perceived ease of use and perceived risk do not significantly affect interest in paying later users. Meanwhile, perceived usefulness, security, and trust have a significant effect on interest in Pay later users.